On the Road to the Word - Derkachova, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
In Moral Letters to Lucilius, Seneca wrote: “It was once more simple because men's sins were on a smaller scale, and could be cured with but slight trouble; in the face, however, of all this moral topsy-turvy men must leave no remedy untried. And would that this pest might so at last be overcome! We are mad, not only individually, but nationally.”